2020
DOI: 10.29303/jppipa.v6i2.424
|View full text |Cite
|
Sign up to set email alerts
|

Development of Student Worksheets Based on Comics to Improve Students' Motivation and Learning Outcomes on Material Vibration, Waves and Sound

Abstract: This research develops a comic-based student worksheet to learn about feasibility, learning outcomes, and motivation of the student worksheet. The research was carried out using research and development (R&D) methods with the ADDIE development model. The implementation of this comic-based Student Worksheet uses a pretest-posttest control group design. The population in this study were students of class VIII at MTsN 3 Banda Aceh. The samples in this study were 57 students in the class of Abu Bakar Ash Siddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Lince (2016) suggests that the thinking process as well as some of the intelligences possessed by students, modalities and learning styles, should be managed as much as possible to become an effective learning strategy. And in its delivery, teachers must also use scientific language in a way that is comfortable in conveying concepts, and motivates students to want to explore information independently (Khaira et al 2020). Ritter et.al (2020) also suggested that practicing creative thinking in learning can improve students' ideation skills and cognitive flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…Lince (2016) suggests that the thinking process as well as some of the intelligences possessed by students, modalities and learning styles, should be managed as much as possible to become an effective learning strategy. And in its delivery, teachers must also use scientific language in a way that is comfortable in conveying concepts, and motivates students to want to explore information independently (Khaira et al 2020). Ritter et.al (2020) also suggested that practicing creative thinking in learning can improve students' ideation skills and cognitive flexibility.…”
Section: Resultsmentioning
confidence: 99%
“…Not only do they use constructivist learning methods, but their teaching materials such as worksheets only measure low-level thinking skills. According to Khaira et al (2020), teachers must apply various innovative strategies to make learning more meaningful, use scientific language in present concepts, and always motivate students to find information independently. One of the strategies used is to create worksheets based on higher-order thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Quality, valid, and practical Student worksheets can be used in the learning process (Khaira et al, 2020;Muskita et al, 2020;Frisilla & Hardeli, 2022;Purwoto, 2022;Sari et al, 2021;Sri et al, 2019). This proves that the valid and practical Student Worksheet for sound and wave materials for junior high school students can be used to determine effectiveness in the learning process.…”
Section: Practicality Of Student Workheetsmentioning
confidence: 99%